Kuat Lentur Balok Laminasi Kombinasi Kayu Jawa (Lannea Coromandelica) dan Gelugu (Cocos nucifera) - Chauf, K.A.; Nurdin, S.; Dolu, A.; Armabelio, A. (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2024)
The use of kayu Jawa (Lannea coromandelica) and gelugu (Cocos nucifera) is very necessary to reduce the forests exploitation as a source of wood raw materials. However, both have debility in terms of mechanical properties and maximum dimensional achievement. Therefore, a mixed glulam system can be applied to produce lightweight structural timber beams with adequate performance. This research is aimed at determining the flexural strength, stiffness, ductility and failure of mixed glulam beams combined with kayu Jawa and Gelugu. A series of bending tests were carried out on timber beams using the three point bending method on three categories of beams, namely B-J, B-G and B-L. B-J beams, consist of solid timber of kayu jawa which has density ± 0,60 gr/cm3, B-K consist of solid gelugu which has density ± 0.88 gr/cm3, while B-L consists of kayu jawa timber in the core zone and one layer of 10 mm thick gelugu with a density of 0,88 gr/cm3 on the tension zone. Each beams category consists of five replications with the dimensions of each beam being 50 mm of wide, 55 mm of high and 760 mm of span. Laminated beams (B-L) are glued with emulsion adhesive with Viscosity 2,500 – 4,500 cPS, resin content 90 – 91%, gel time: 1 hour and curing time 5 – 6 hours with two-sided coating of 250 gr/m2 and clamping force 2 MPa. The results of this research show that the flexural strength (fb) and stiffness (EI) of mixed glue laminated laminated beams are 1,3 times higher than B-J. Apart from that, mixed glue laminated laminated beams (B-L) there was an increase the ductility of 47% when compared to B-G.